A new cryptic, rupicolous species of Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from Meghamalai, Tamil Nadu, India - Chaitanya, R.; Lajmi, Aparna; Giri, Varad B. (Zootaxa, 2018)
A distinct new gecko of the genus Hemidactylus is described from the Meghamalai massif in Tamil Nadu, India. This large sized (average SVL 88.2±16.0 to at least 112.2 mm), cryptic, rock-dwelling species is superficially similar to its tuberculate South Asian congeners of comparable size, but can be distinguished from them in having 17–19 longitudinal rows of fairly regularly arranged, strongly keeled, striated tubercles with the two most medial parasagittal rows smaller, flatter, strongly keeled and rounded, increasing in size laterally and becoming strongly conical at the flanks; 8–10 and 10–12 sub-digital lamellae under the first and fourth digits respectively of both manus and pes; 17–22 femoral pores on each side separated medially by a diastema of 10–11 poreless scales; 11–15 supralabials and 9–14 infralabials. Molecular data supports the distinctiveness of this species and helps ascertain its phylogenetic position within the larger Indian Hemidactylus clade.